STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM IMPLEMENTASI DISIPLIN POSITIF: STUDI KUALITATIF DI SDN 02 CIKAWUNG KABUPATEN BANYUMAS - Isna Nur Istiqomah; Siswadi Siswadi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The shift in educational paradigms from punitive to positive discipline requires a strategic role for principals in managing changes in school culture toward a more humanistic and educative one. This study aims to analyze the principal's leadership strategies in implementing positive discipline for teachers and students at SDN 02 Cikawung, Banyumas Regency, which integrates local wisdom values. Using qualitative descriptive methods, data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldana. The results revealed that the principal fulfills his role as educator, manager, and supervisor through three key strategies: internalizing values ​​through role models, strengthening teacher capacity through reflective coaching, and creating a child-friendly school ecosystem. A unique finding of this study is the application of the